2022
DOI: 10.3390/diagnostics13010121
|View full text |Cite
|
Sign up to set email alerts
|

TLRs Gene Polymorphisms Associated with Pneumonia before and during COVID-19 Pandemic

Abstract: Background: The progression of infectious diseases depends on the characteristics of a patient’s innate immunity, and the efficiency of an immune system depends on the patient’s genetic factors, including SNPs in the TLR genes. In this pilot study, we determined the frequency of alleles in these SNPs in a subset of patients with pneumonia. Methods: This study assessed six SNPs from TLR genes: rs5743551 (TLR1), rs5743708, rs3804100 (TLR2), rs4986790 (TLR4), rs5743810 (TLR6), and rs3764880 (TLR8). Three groups o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The study by Salamaikina et al (2022) with a Russian population was the only study to date investigating this SNP and COVID-19; however, it had a different objective from this present study, which was to compare the allele frequencies of genetic polymorphisms in TLR genes in samples obtained from individuals with pneumonia in the period before the appearance of SARS-CoV-2 and during the COVID-19 pandemic in this same population and with international public data from the European population. In contrast to the results of this present research, they concluded that Russian individuals with the mutant allele (C) of the SNP rs3804100 have a 0.32-fold greater vulnerability to COVID-19 pneumonia compared to the group of healthy people [99].…”
Section: Discussioncontrasting
confidence: 99%
“…The study by Salamaikina et al (2022) with a Russian population was the only study to date investigating this SNP and COVID-19; however, it had a different objective from this present study, which was to compare the allele frequencies of genetic polymorphisms in TLR genes in samples obtained from individuals with pneumonia in the period before the appearance of SARS-CoV-2 and during the COVID-19 pandemic in this same population and with international public data from the European population. In contrast to the results of this present research, they concluded that Russian individuals with the mutant allele (C) of the SNP rs3804100 have a 0.32-fold greater vulnerability to COVID-19 pneumonia compared to the group of healthy people [99].…”
Section: Discussioncontrasting
confidence: 99%
“…Despite the small sample size in our current investigation, it is noteworthy that analogous studies have previously performed association analyses in similarly small sample sizes to gain initial insights before undertaking extensive validation endeavors in larger populations [46][47][48]. In line with these previous reports, our study conducted a preliminary analysis within a limited cohort, revealing no association between TLR7 (rs864058) polymorphism and susceptibility to COVID-19.…”
Section: Discussionsupporting
confidence: 49%
“…Additionally, it has been established that progressive pneumonia virus susceptibility is affected by the effects of ovine TMEM154 gene polymorphisms after normal exposure [ 26 ]. In humans, TLRs gene polymorphisms have been reported to be associated with pneumonia [ 44 ].…”
Section: Discussionmentioning
confidence: 99%